Wonder Woman. Warbringer - Bardugo, Leigh (DC icons., 2019)
When Princess Diana breaks Amazon law and saves a mortal girl, she has no idea her actions could negatively impact the world. And the girl she saved, Alia Keralis, had no idea she is a Warbringer--destined to bring bloodshed and agony to the world. Now the unlikely friends will have to stand side-by-side in order to save both their worlds.